High reflectivity metamaterial of close-packed dielectric spheres. (16th February 2018) - Zipp, Lucas J; Slovick, Brian A; Krishnamurthy, Srini
Abstract: We present a design for an ultra-high reflectivity metamaterial that can be synthesized by self-assembly methods. This is in contrast to current metamaterial reflector designs which require lithographic fabrication methods, or traditional multilayer dielectric films which depend on careful deposition techniques, both of which are not suitable for scaling to large surface areas. By exploiting the Mie resonance in dielectric spheres and optimizing the sphere size and coating thickness, we apply full-wave simulations to obtain near-perfect reflection in the near-infrared spectral wavelength region. We report the results of our systematic study on angular performance and the effect of coating thickness, particle size distribution, voids, and number of layers on the reflectivity of the metamaterial.